Effect of Mercury on Seed Germination and Seedling Growth of Mungbean (Vigna radiata (L.) Wilczek) - ZI Muhammad; KS Maria; A Mohammad; S Muhammad; F Zia-ur-Rehman; K Muhammad (Journal of Applied Sciences and Environmental Management)
Among the toxic elements release in the environment, mercury is considered highly toxic to the growth of plants. The present studies report the effects of different concentrations (1, 3, 5 and 7 mM) of mercury on seed germination and seedling growth performance of mungbea (Vigna radiata) as compared to control. Mercury treatment in the form of mercuric chloride at 1 mM did not show significant reduction in seed germination of V. radiata as compared to control. Increase in  concentration of mercury to 3 mM produced significant (p<0.05) reduction in seed germination. Mercury treatment at 7 mM-produced significant (p<0.05)  reduction in seedling and root length of the plants. The increase in concentration of mercury treatment at 7 mM was found sufficient to cause significant reductions in seedling dry weight of as compared to control. Mercury treatment at all concentrations decreased seed germination, shoot, and root length and seedling dry weight. Increase in mercury concentration upto 7 mM showed highest percentage of decrease in seed germination (42%), seedling length (70%), root length  (66%) and seedling dry weight (47%) of mungbean as relation to control. V. radiata were more sensitive to mercury stress in seedling growth and root elongation than seed germination. The seedlings of V. radiata showed greater tolerance to mercury at 1 mM (85.83 %) and lowest at 7 mM (34.13%). These results show that there is a negative effect towards germination and growth of mungbean by mercury treatment. Minimum use of the mercury containing compounds in fungicide,  pesticide and nematicide is recommended. Special care should be taken to monitor the toxic pollutants available in the immediate environment. The accumulation of such types of toxic pollutants in larger concentrations by crop can produce harmful effects to crops and ecosystem as well.